Methods for the Evaluation of the Competitiveness of Energy Companies - Chebotareva, Galina Sergeevna (Economy of Regions, 2018)
The strategic tasks of energy companies are impossible to achieve without reducing the risks of companies’ development because it is an element of increasing the companies’ competitiveness. The article is devoted to the evaluation of the competitiveness of Ural energy companies. For further deterministic evaluation, the author introduces the interpretation of competitiveness as the sum of development risks of an energy company. The article presents a comprehensive assessment of the competitiveness of an energy company on the basis of the proposed methodological approach. This approach includes the assessment and ranking of energy company’s risks, the comparative analysis of real and threshold values of the overall risk of investment project implemented by a company. I tested the method of scenario analysis. The main criterion of this method is the consumers demand on energy resources. I applied the theory of economic capital as an auxiliary instrument. Risks’ rating construction is one of the most significant results of the method’s approbation. On the basis of the calculated indicators of the overall risk, I have developed a map of competitiveness. This map allows assessing the twelve cases of company’s competitiveness depending on different development scenarios and types of economic capital. The practical value of this map lies in the possibility to conduct a comparative assessment of overall risk. Furthermore, I have calculated the monetary equivalent of overall risk in each of twelve competitiveness states. The comparative assessment along with the monetary equivalent of overall risk allow making reasonable administrative decisions on the development of the most effective programs of risk management. The obtained results have theoretical and practical importance and can be used firstly in the development of a methodology for assessing competition in the national and global energy markets. Secondly, these results can be useful for the development and improvement the effectiveness of risk management in energy companies. Further research can focus on developing a specific approach for the assessment of the actual economic capital of an energy company, specifying an indicator of economic losses in a case of default, etc.